2017
DOI: 10.1007/s11695-017-2595-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bariatric Surgery on Metabolic and Gut Microbiota Profile: a Systematic Review and Meta-analysis

Abstract: We aim to review the available literature on obese patients treated with bariatric procedures, in order to assess their effect on the metabolic and gut microbiota profiles. A systematic literature search was performed in PubMed, Cochrane library, and Scopus databases, in accordance with the PRISMA guidelines. Twenty-two studies (562 patients) met the inclusion criteria. This study points to significant amelioration of postoperative levels of glucose, insulin, triglycerides, total cholesterol, LDL, HDL, HOMA-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 48 publications
5
76
1
5
Order By: Relevance
“…Preliminary work in humans supports that those with T2D have a reduced abundance of Bacteroidetes and a higher abundance of Firmicutes (45), and one experimental study showed that transfer of gut microbiota from individuals who were lean to those with metabolic syndrome, improved gut microbiome diversity and insulin sensitivity among the recipients (46). Further, a comprehensive systematic review and meta-analysis recently documented that gastric bypass surgery, which contributes to weight loss and a reduced risk of T2D, also leads to changes in gut microbiota composition, particularly enrichment of Bacteroidetes (47). …”
Section: Overview Of Homeostatic Brain-body Pathwaysmentioning
confidence: 99%
“…Preliminary work in humans supports that those with T2D have a reduced abundance of Bacteroidetes and a higher abundance of Firmicutes (45), and one experimental study showed that transfer of gut microbiota from individuals who were lean to those with metabolic syndrome, improved gut microbiome diversity and insulin sensitivity among the recipients (46). Further, a comprehensive systematic review and meta-analysis recently documented that gastric bypass surgery, which contributes to weight loss and a reduced risk of T2D, also leads to changes in gut microbiota composition, particularly enrichment of Bacteroidetes (47). …”
Section: Overview Of Homeostatic Brain-body Pathwaysmentioning
confidence: 99%
“…Roux‐en‐Y gastric bypass (RYGB) surgery results in significant and long‐term weight loss with significant reduction of incidence and remission of type 2 diabetes, hypertension, and dyslipidemia . According to a meta‐analysis by Magouliotis et al, glucose, insulin, triglycerides, total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), and homeostatic model assessment of insulin resistance (HOMA‐IR) were significantly lowered, indicating improvement in metabolic health following bariatric surgery …”
Section: Introductionmentioning
confidence: 99%
“…1 According to a meta-analysis by Magouliotis et al, glucose, insulin, triglycerides, total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), and homeostatic model assessment of insulin resistance (HOMA-IR) were significantly lowered, indicating improvement in metabolic health following bariatric surgery. 2 Metabolites are small molecules that are substrates, intermediates, or products of biological processes. 3 "Metabolomics" refers to comprehensive profiling of metabolites present in cells, tissues, or whole organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The immediate caloric decrease after bariatric surgery is caused by a substantial reduction in hunger and an increase in satiation (10). The role of anatomical restrictions of the ventricle and nonmechanical factors, such as gut hormones, bile acids, and gut microbiota, remain under investigation (11)(12)(13). However, little is known about the associations between changes in total energy intake and energy-contributing nutrients (i.e., the macronutrients carbohydrates, fat, and protein) and the long-term weight change in patients who have undergone bariatric surgery (14).…”
Section: Introductionmentioning
confidence: 99%